1990
DOI: 10.1200/jco.1990.8.2.266
|View full text |Cite
|
Sign up to set email alerts
|

Stomach conservation in stages IE and IIE gastric non-Hodgkin's lymphoma.

Abstract: Thirty-four patients with stages IE and IIE gastric lymphoma were treated with chemotherapy and radiotherapy combinations without stomach resection. In 20 patients, the diagnosis was established by endoscopic biopsy only; the other 14 had laparotomy and biopsy. No patient had a gastrectomy before treatment. Nineteen patients had stage IE disease and 15 had stage IIE. Lymphoma diagnoses were: diffuse large-cell, 26; immunoblastic, three; diffuse well-differentiated, three; nodular mixed, one; and unclassified, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
61
0
3

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(67 citation statements)
references
References 7 publications
3
61
0
3
Order By: Relevance
“…However, the overall survival rate achieved in patients who underwent debulking surgery and CHOP chemotherapy in that study (5-year rate, 79%) was similar to the overall survival rate observed in patients who were treated at the M. D. Anderson Cancer Center with chemotherapy and radiotherapy without undergoing debulking surgery (5-year rate, 73%). 19 In the latter study, none of the 34 patients developed stomach perforation or bleeding after nonsurgical treatment, and 24 of 26 surviving patients (92%) were able to retain their stomachs. Similarly, Perren et al 20 have recommended chemotherapy and radiotherapy without surgery for women with bulky lymphomas involving the cervix or upper vagina.…”
Section: Discussionmentioning
confidence: 84%
“…However, the overall survival rate achieved in patients who underwent debulking surgery and CHOP chemotherapy in that study (5-year rate, 79%) was similar to the overall survival rate observed in patients who were treated at the M. D. Anderson Cancer Center with chemotherapy and radiotherapy without undergoing debulking surgery (5-year rate, 73%). 19 In the latter study, none of the 34 patients developed stomach perforation or bleeding after nonsurgical treatment, and 24 of 26 surviving patients (92%) were able to retain their stomachs. Similarly, Perren et al 20 have recommended chemotherapy and radiotherapy without surgery for women with bulky lymphomas involving the cervix or upper vagina.…”
Section: Discussionmentioning
confidence: 84%
“…[13][14][15][16][17][18]30,31,45,46 Although past studies showed that surgical resectability was of significance, recent studies have demonstrated that nonsurgical strategies and surgery-based modalities had an equivalent efficacy. 30,31,45 Based on all these observations, and taking patients' quality of life into consideration, nonsurgical treatment is an alternative and optimal therapeutic modality for gastrointestinal lymphoma. Further randomized prospective studies with a large number of patients are still needed to establish …”
Section: Discussionmentioning
confidence: 99%
“…Mortality directly related to total gastrectomy can be as high as 4% [81]. Favorable experiences with local radiotherapy, chemotherapy, and antibody therapy, allowing for gastric preservation, have limited the role of surgery even in patients failing primary therapy, although surgery may still be required for complications [82].…”
Section: Surgerymentioning
confidence: 99%